2014
DOI: 10.1186/1476-4598-13-212
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 inhibits p57Kip2 expression in prostate cancer

Abstract: Backgroundp57Kip2, a cyclin-dependent kinase inhibitor, is considered to be a candidate tumor suppressor gene that has been implicated in Beckwith-Wiedemann syndrome and sporadic cancers. In addition, decreased expression of p57Kip2 protein has been frequently observed in pancreatic, lung, breast, bladder, gastrointestinal tract and prostate cancers. However, p57Kip2 gene mutations are rare in these cancers suggesting that other unknown mechanisms might be at play in reducing its expression. The aim of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…miR-21, a signature miR of dairy milk, is overexpressed in PCa cells [304,305], in blood serum [304,306], PBMCs [307], serum exosomes [308] well as urinary exosomes of PCa patients [309,310]. miR-21 is regarded as an oncomir, that inhibits pivotal tumor suppressor genes such as PTEN, p57kip2 (CDKN1C), PDCD4, MARCKS and others [240,[311][312][313][314]. Loss of function of the PTEN tumor suppressor, upregulating the phosphoinositide 3-kinase (PI3K)-AKT signaling network, is recognized as one of the most common driving events in PCa development [311].…”
Section: Prostate Cancermentioning
confidence: 99%
“…miR-21, a signature miR of dairy milk, is overexpressed in PCa cells [304,305], in blood serum [304,306], PBMCs [307], serum exosomes [308] well as urinary exosomes of PCa patients [309,310]. miR-21 is regarded as an oncomir, that inhibits pivotal tumor suppressor genes such as PTEN, p57kip2 (CDKN1C), PDCD4, MARCKS and others [240,[311][312][313][314]. Loss of function of the PTEN tumor suppressor, upregulating the phosphoinositide 3-kinase (PI3K)-AKT signaling network, is recognized as one of the most common driving events in PCa development [311].…”
Section: Prostate Cancermentioning
confidence: 99%
“…Importantly, daily milk consumption during adolescence ( vs. less than daily), but not in midlife or currently, was associated with a 3.2-fold risk of advanced prostate cancer [ 253 ], pointing to a critical signaling magnitude of mTORC1-dependent prostate branching morphogenesis during adolescence [ 254 ], the prostate’s period of sexual maturation [ 246 ]. There is accumulating evidence that microRNA-21 contributes to prostate cancer pathogenesis interfering with multiple pathways including mTORC1-dependent translation and cell proliferation [ 255 , 256 , 257 , 258 ]. In fact, addition of commercial cows' milk to LNCaP prostate cancer cells stimulated growth of prostate cancer cells and increased the growth rate of the tumor cells over 30% [ 259 ].…”
Section: Milk-mediated Over-activation Of Mtorc1 and Age-related Dmentioning
confidence: 99%
“…Depletion of p57Kip2 but not p21Cip1 rendered IGF-1 or insulin sufficient to induce cellular proliferation in the absence of EGF. Remarkably, microRNA-21, a major microRNA of commercial milk [ 111 , 117 ], has recently been shown to target p57Kip2 in prostate cancer cells [ 256 ]. Increased levels of microRNA-21 have been found in serum and mammary tumor tissue of breast cancer patients [ 273 , 274 , 275 , 276 ].…”
Section: Milk-mediated Over-activation Of Mtorc1 and Age-related Dmentioning
confidence: 99%
“…Interestingly, miR-21 was identified as one of the oncomiRs whose expression was found to be upregulated in many types of cancer, including both solid tumors and breast cancer [70]. Mechanistically, upregulation of miR-21 expression leads to the suppression of several key tumor suppressor genes, such as p57 Kip2 , tropomyosin 1 (TPM1), programmed cell death protein 4 (PDCD4) and PTEN [71][72][73][74]. Indeed, it was also confirmed that miR-21 antisense oligos inhibited the proliferation and invasion of primary stromal cells of phyllodes tumors [70].…”
Section: Mirna-based Therapeutics For Tamoxifen Resistancementioning
confidence: 99%